L’écrit et la justice au Mont Saint-Michel : les notices narratives (vers 1060-1150) - Éric Van Torhoudt (Tabularia)
The practices in the Mont as regards judiciary writings are comparable to the ones of the ligerian monasteries. The series of narrative notices kept in the cartulary begins under the rule of abbot Renouf (1055-1084/1085), thrives with abbot Bernard (1131-1149) and ends with the beginning of the writing of the cartulary towards 1149/1150. The form of these writings follows the diplomatic and historiographic tradition of the scriptorium of the Mont St Michel and finds a natural place in the chronic cartulary. The monks stage in them their autonomy from the earls or the bishops and underline the qualities of some of their abbots. The seven examples studied here are records of agreements which qualify themselves as pacta or conventiones. These texts putting together diplomatic formulas, excepts from previous charts and narrative episodes, are patchworks which display alternatively subjective and objective styles so as to recreate an unchanging scenario leading to the repentance of the laymen. The exceptional procedure of the judicium is only one element of a negotiation in which a large array of friends, parents, people endowed with authority, laymen or ecclesiastics, intervene, not to “say the law” or execute a sentence, but to validate a written proof or protect their own interests. The purpose is not the application of a judicial norm, but the appeasement of feuds and the restoration of concord through compromise and the renewing of the social links. To understand these texts requires the ability to read “between the lines” and to pay much heed to the implicit part of them.